2010
DOI: 10.1038/nrc2900
|View full text |Cite
|
Sign up to set email alerts
|

Functional proteomics to dissect tyrosine kinase signalling pathways in cancer

Abstract: Therefore, it is only by studying the proteome that we can extract functional understanding of the pathways that are deranged in cancer. Rather than just identifying proteins, functional proteomics focuses on the generation of information about proteins, such as expression levels, PTMs and activity, which directly contribute to a functional understanding of the biological system.Functional proteomics feeds directly into the systematic analysis of biochemical networks, often using mathematical modelling or othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
133
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(138 citation statements)
references
References 148 publications
3
133
0
2
Order By: Relevance
“…Also, numerous studies have identified key signaling molecules and pathways that are activated by oncogenic tyrosine kinases (OTKs) and participate in mediating their effects on malignant transformation (45,55,57,71,72,75). However, besides triggering positive signaling events, OTKs also need to overcome negative regulatory constraints to drive tumor initiation and/or progression (7,24,42,57).…”
mentioning
confidence: 99%
“…Also, numerous studies have identified key signaling molecules and pathways that are activated by oncogenic tyrosine kinases (OTKs) and participate in mediating their effects on malignant transformation (45,55,57,71,72,75). However, besides triggering positive signaling events, OTKs also need to overcome negative regulatory constraints to drive tumor initiation and/or progression (7,24,42,57).…”
mentioning
confidence: 99%
“…Dysregulation of the EGFR signaling pathway through overexpression or hyperactivation is associated with tumor development (23,25,26). A meta-analysis demonstrated that the rate of EGFR overexpression in ESCC is high and EGFR expression levels are a potential predictor of the T stage (tumor-node-metastasis classification system) (27), vascular invasion and overall survival (27).…”
Section: Discussionmentioning
confidence: 99%
“…24 This signaling cascade has an amplification effect and is tightly controlled by numerous negative and positive regulators, and mis-activation of Erk can lead to numerous defects including cancer. 25 Recently it has been found that miRNAs are involved in the control of Erk activation in cardiac fibroblasts where miR-21 negatively regulates expression of the FGF signaling inhibitor, Sprouty. (a-D') Dicer -/-embryos express normal levels of Nodal, the Nodal co-activator Cripto and the Nodal convertases Spc1, 15 and Spc4.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%